Death Path Illustration in the Old and New Testament - NAJAFI, SALIMEH; HAJIESMAEILI, MOHAMMADREZA; MOTIA, MAHDI (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Religious traditions that wait for the end of the world, believe that it is imminent. According to them, the world has been lost in the current system, the death will come, and the creation will stand. Consequently, in the opinion of Jesus’ followers, he was a man chosen by God, the promised Messiah of David’s generation, who was harassed and crucified because of Adam’s sin. On the third day, he ascended to heaven, changed the image of death by his ascension and determined the way of reward and punishment by his returned. RESUMEN Las tradiciones religiosas que esperan el fin del mundo, creen que este es inminente. Según ellas, el mundo se ha perdido en el sistema actual, vendrá la muerte y la creación permanecerá. En consecuencia, en opinión de los seguidores de Jesús, él era un hombre elegido por Dios, el Mesías prometido de la generación de David, quien fue acosado y crucificado por el pecado de Adán. Al tercer día, ascendió al cielo, cambió la imagen de la muerte con su ascensión y determinó el camino de la recompensa y el castigo con su regreso.